PERCEIVED EASE OF USE, SOCIAL INFLUENCERS, FACILITATING CONDITIONS, USER EXPERIENCE ON THE INFLUENCE OF HUMAN-MACHINE INTERACTION ON INTERACTION EFFICIENCY, EMOTIONAL IMPACT OF USING CHAT GPT - Ajeng Ayu Wulandari; Titih Nurhaipah; Noviawan Rasyid Ohorella (Universitas Gunadarma, 2023)
This research analyzes the impact of Perceived Ease of Use, Social Influence, Facilitating Conditions, and User Experience in GPT Chat and how it affects Interaction Efficiency and Emotional Impact of communication interactions with machines. The theoretical frameworks are the Unified Theory of Technology Acceptance and Use (UTAUT) and Human Machine Interaction (HCI). Data was collected through a questionnaire with a Likert scale and tested on 100 respondents using the Purposive Sampling method among Chat GPT users. The research results reveal that five variables, namely Perceived Ease of Use, Facilitating Conditions, and User Experience, positively and significantly influence Interaction Efficiency and Emotional Impact. Still, the Social Influence variable does not substantially affect User Experience Perceived Ease of Use, and The UTAUT model contributes 17.7% to User Experience. In contrast, User Experience contributes 5.6% to Interaction Efficiency, and Interaction Efficiency contributes 517.9% to Emotional Impact.